2022
DOI: 10.1186/s12902-022-01242-w
|View full text |Cite
|
Sign up to set email alerts
|

Effect of liver dysfunction on outcome of radioactive iodine therapy for Graves’ disease

Abstract: Liver dysfunction is a common complication of Graves’ disease (GD) that may be caused by excessive thyroid hormone (TH) or anti-thyroid drugs (ATDs). Radioactive iodine (RAI) therapy is one of the first-line treatments for GD, but it is unclear whether it is safe and effective in patients with liver dysfunction. 510 consecutive patients with GD receiving first RAI were enrolled in the study, and followed up at 3-, 6- and 12-month. Liver dysfunction was recorded in 222 (43.5%) patients. GD patients with liver d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…In this study, the level of FSH was significantly higher in the patient group as compared to its level in the control group for all groups. It was observed that the levels of the hormone in the (26-35 years old) and (36-45 years old) groups of patients were higher than that in the (15-25 years old) group, as shown in Table (2). In this study, it was observed the level of FSH is affected by aging; the results revealed a significant increase of FSH with the increase of age [16].…”
Section: The Level Of Fsh In Patient Group In Comparison To the Contr...mentioning
confidence: 57%
See 1 more Smart Citation
“…In this study, the level of FSH was significantly higher in the patient group as compared to its level in the control group for all groups. It was observed that the levels of the hormone in the (26-35 years old) and (36-45 years old) groups of patients were higher than that in the (15-25 years old) group, as shown in Table (2). In this study, it was observed the level of FSH is affected by aging; the results revealed a significant increase of FSH with the increase of age [16].…”
Section: The Level Of Fsh In Patient Group In Comparison To the Contr...mentioning
confidence: 57%
“…Obesity, diabetes, and even cancer are all increased in risk by liver dysfunction [1]. Several other hormonal illnesses, such as Graves' disease (GD), are associated with liver impairment [2]. Both excess and deficiency of adrenal activity can cause changes in liver function, and adrenocortical dysfunction can occur in cirrhotic individuals, particularly during periods of decompensation.…”
Section: Introductionmentioning
confidence: 99%
“…The patient was initially diagnosed with hyperthyroid-related liver injury complicated by paroxysmal atrial fibrillation. Research [ 17 ] and guidelines [ 2 , 13 , 16 ] suggested that 131 I treatment can be given priority to GD with heart disease and hepatic insufficiency. Research [ 11 ] and guidelines [ 2 ] also recommend long-term drug therapy for patients with senile hyperthyroidism who are unwilling to receive 131 I therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the liver is a major site for the production of albumin, transthyretin and thyroxine-binding globulin proteins that bind thyroid hormones [ 38 ]. Consequently, a hyperthyroid state is associated with various chronic disorders such as cardiovascular diseases, diabetes and liver diseases [ 39 ], and impaired both the hepatic structure and function [ 4 , 40 ]. Additionally, the prevalence of liver dysfunction in patients with hyperthyroidism has been estimated to be between 37% and 77.9% [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Radioactive iodine and thyroidectomy represent alternative treatments for hyperthyroidism, with a promising prognosis and low relapse rates. However, achieving a balance in the thyroid axis between hyperthyroidism and hypothyroidism can be challenging [ 4 ]. The dysregulation of thyroid hormone production and secretion may lead to an overall increase in metabolism, resulting in a high demand for the synthesis of chemical energy through a series of oxidation-reduction reactions.…”
Section: Introductionmentioning
confidence: 99%